Wind-tunnel research on the mechanics of plumes in the atmosphere surface layer - Poreh, Michael, author; Shrivastava, P. K. (Prakash K.), author; Cermak, Jack E., author; Fluid Mechanics and Wind Engineering Program, Fluid Dynamics and Diffusion Laboratory, Department of Civil Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1983)
The diffusion of a neutrally buoyant gas emitted from point sources into neutral, stable and unstable boundary layers that simulated atmospheric conditions were studied in a meteorological wind tunnel for flow over two surface roughnesses. Measurements were made of the mean flow velocities and temperatures, turbulence intensities, velocity correlations and gas concentrations in the diffusing plume. Empirical models were developed for predicting diffusion under all three stabilities studied.
Project No. 5-3 2512.
Prepared for Department of the Army, U.S. Army Armament Research and Development Command, Chemical Systems Laboratory, Aberdeen Proving Ground.
CER83-84JEC-PKS-MP12.
Keywords: Wind tunnel models; Boundary layer (Meteorology); Atmospheric diffusion